The Effect of Pancasila and Civic Education Learning on Friendly/Communicative Character - Alifah Nurfadilah; Damanhuri Damanhuri; Febrian Alwan Bahrudin (Universitas Muhammadiyah Enrekang, 2023)
This study aims to find out the effect of Pancasila and Civic Education on friendly/communicative character in students of the Secondary Education Affirmation program (ADEM) at Serang Public High School 2. This research is an experimental type that uses quantitative approach. The results obtained from the entire pre-conditional test that has been performed have meets the assumption of each test (normal, linearly, homogenity), and the final result is the result of a simple regression test showing that there is an effect of Pancasila and Civic Education learning on the friendly/communicative character in students of the Secondary Education Affirmation program at Serang Public High School 2 significantly with positive effect direction. Therefore in the following research, there is an effect between of Pancasila and Civic Education learning on friendly/communicative character.